Vaccine based on folded receptor binding domain‐PreS fusion protein with potential to induce sterilizing immunity to SARS‐CoV‐2 variants. Issue 8 (15th April 2022) - Gattinger, Pia; Kratzer, Bernhard; Tulaeva, Inna; Niespodziana, Katarzyna; Ohradanova‐Repic, Anna; Gebetsberger, Laura; Borochova, Kristina; Garner‐Spitzer, Erika; Trapin, Doris; Hofer, Gerhard; Keller, Walter; Baumgartner, Isabella; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is responsible for the ongoing global COVID‐19 pandemic. One possibility to control the pandemic is to induce sterilizing immunity through the induction and maintenance of neutralizing antibodies preventing SARS‐CoV‐2 from entering human cells to replicate in. Methods: We report the construction and in vitro and in vivo characterization of a SARS‐CoV‐2 subunit vaccine (PreS‐RBD) based on a structurally folded recombinant fusion protein consisting of two SARS‐CoV‐2 Spike protein receptor‐binding domains (RBD) fused to the N‐ and C‐terminus of hepatitis B virus (HBV) surface antigen PreS to enable the two unrelated proteins serving as immunologic carriers for each other. Results: PreS‐RBD, but not RBD alone, induced a robust and uniform RBD‐specific IgG response in rabbits. Currently available genetic SARS‐CoV‐2 vaccines induce mainly transient IgG1 responses in vaccinated subjects whereas the PreS‐RBD vaccine induced RBD‐specific IgG antibodies consisting of an early IgG1 and sustained IgG4 antibody response in a SARS‐CoV‐2 naive subject. PreS‐RBD‐specific IgG antibodies were detected in serum and mucosal secretions, reacted with SARS‐CoV‐2 variants, including the omicron variant of concern and the HBV receptor‐binding sites on PreS of currently known HBV genotypes. PreS‐RBD‐specific antibodies of the immunized subject more potently inhibited the interaction of RBD with its human receptor ACE2 and their virus‐neutralizing titers (VNTs) were higher than median VNTs in a random sample of healthy subjects fully immunized with registered SARS‐CoV‐2 vaccines or in COVID‐19 convalescent subjects. Conclusion: The PreS‐RBD vaccine has the potential to serve as a combination vaccine for inducing sterilizing immunity against SARS‐CoV‐2 and HBV by stopping viral replication through the inhibition of cellular virus entry. Abstract : This study reports the design and characterization of a SARS‐CoV‐2 subunit vaccine (PreS‐RBD). PreS‐RBD, but not RBD alone, induces RBD‐specific IgG1 and long‐lasting IgG4 in serum and mucosal fluids, and cross‐reacts with SARS‐CoV‐2 variants of concern. PreS‐RBD‐specific antibodies of the immunized subject more potently inhibit the interaction of RBD with angiotensin converting enzyme 2 (ACE2), and their virus‐neutralizing titers are higher than median titers in a random sample of healthy subjects fully immunized with registered SARS‐CoV‐2 vaccines or in COVID‐19 convalescent subjects.Abbreviations: COVID‐19, coronavirus disease 2019; IgG, immunoglobulin G; HBV, hepatitis B virus; RBD, receptor‐binding domain; PreS, HVB domain; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2